PHARMACOEPIDEMIOLOGICAL EVALUATION OF HIV PHARMACOTHERAPY AT DISTRICT ART CENTER IN SOUTH TELANGANA - B, SONALI; G, AKHILA; R, DIVYA; R ADEPU,; T, ANUSHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Objective of the study was to assess the drug utilization pattern of antiretroviral drugs, and medication adherence behavior among human immunodeficiency virus (HIV) patients attending a local ART center, Suryapet, South Telangana. Methods: This was a prospective observational study approved by institutional ethics committee. Demographic, clinical, laboratory, and the treatment details were collected on daily basis for new cases and the data add on was collected for old cases. Medication adherence behavior was assessed through Morisky Medication Adherence Scale-8. Results: During the study period, a total of 505 HIV patients were enrolled. Among them, majority patients were women (61%), in the age group of 31–45 (49.7%). Illiterates (52.6%). Major mode of transmission identified was intimate contact (74%), and majority patients were in Stage I (49%). TLE regimen was prescribed in 69.9% patients and for children the prescribed regimen was ABC, 3TC, EFV (5.1%). About 43% patients were found with medium adherence. Conclusion: This study concludes that the most prescribed regimens were combination of TLE, and majority of the patients were found with medium adherence.